Art and science of psychopharmacology : essential tools for treating anxiety, depression, bipolar disorder & psychosis - Marie, Susan (PESI Publishing & Media, 2020)
This book guides you through the various medications for each of these diagnoses and how to form essential conversations around your client's prescription. Susan Marie's decades of practice as a psychiatric nurse practitioner and educator shine through with lively case examples, discussion of complementary and alternative methods, and clear considerations for special and vulnerable populations.